SPECIFIC ASPECTS OF THE JADIDISM MOVEMENT AGAINST THE COLONIAL POLICY IN TURKESTAN (Scientific journal of the Fergana State University, 2024)
This article analyzes the emergence of the Jadidist movement and its impact on political life. Also, the main scientific features of the Jadidism movement and the fundamental essence of the main ideas they put forward are based. At the same time, the main essence of the actions of new-minded intellectuals among the population of Turkestan against colonial oppression is revealed based on their philosophical factors.